Документарні операції як важливий сегмент комерційного банкінгу - Моторнюк, У. І.; Ноджак, Л. С. (Видавництво Львівської політехніки, 2012)
Проаналізовано досвід застосування документарних операцій у світовій та вітчизняній практиці в умовах глобалізації банківської діяльності, а також посилення конкуренції у банківському середовищі та виходу українських банків на міжнародні фінансові ринки. The world and domestic experience of documentary transactions in the context of globalization of banking, as well as increased competition in the banking environment and the entry of Ukrainian banks in to international financial markets has been analyzed in the article.
Documentary transactions as the important segment of commercial banking
Keywords: глобалізація банківської діяльності; комерційний банкінг; документарні операції; документарний акредитив; документарне інкасо; банківська гарантія; портфель документарних операцій; globalization of banking; commercial banking; documentary transactions; documentary Letter of Credit; documentary collections; bank guarantee; documentary transactions portfolio